Sorting them all out: Exploring the separable phrasal verbs of English. (August 2018) - Gardner, Dee; Davies, Mark
Abstract: Several studies in recent years have addressed the impact of phrasal verbs in the English language in an attempt to improve teaching and inform research. While some experts have mentioned the problematic case of separability with these structures, no major attempt to quantify and qualify separable phrasal verbs (SPVs) has been undertaken. Given the prolific nature of these structures, and the documented difficulty they pose for learning and research, we attempt to partially address this issue by finding, counting, and analyzing the SPVs in a mega-corpus of over 1.3 billion words of American and British English. Specifically, we provide and discuss lists of the most frequent SPVs overall, and for those separated by one, two, and three intervening words. We also provide data regarding separability preferences among prolific SPVs, as well as typical grammatical structures of the intervening words between verbs and their allied particles. Implications for instruction and research are discussed throughout the article.